2020
DOI: 10.3390/su12104078
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation for Teachers and Students in Higher Education

Abstract: It is time to undertake changes in the evaluation methods we use, especially in higher education. These changes in the actors responsible for evaluation would combine hegemonic traditional evaluating processes with other, more democratic modalities, which would turn the predominantly institutional rating purposes of evaluation into a learning experience, and develop a competence in evaluation in students. Only in this way can coherence be achieved within the context of the student’s initiative and the construc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 30 publications
0
6
0
1
Order By: Relevance
“…Nevertheless, the process is not exempt from difficulties [14], as this research has revealed. These difficulties not only appear in the assessing process but also in the calculation of the multiple assessments; therefore, the use of specific platforms, designed by some authors [1], is advised. The bibliometric study conducted by [22] warns that it is also required to elucidate the typologies, models, and specific assessment practices alternative to the traditional ones by means of a formal exam.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Nevertheless, the process is not exempt from difficulties [14], as this research has revealed. These difficulties not only appear in the assessing process but also in the calculation of the multiple assessments; therefore, the use of specific platforms, designed by some authors [1], is advised. The bibliometric study conducted by [22] warns that it is also required to elucidate the typologies, models, and specific assessment practices alternative to the traditional ones by means of a formal exam.…”
Section: Discussionmentioning
confidence: 99%
“…Assessment is an essential, particular, and delicate element within the learningteaching process, with manifesting implications on other elements (aim, content, and competence identification, as well as for method, grouping, activity, and resource selection). It constitutes the first, the last, and the recurring element [1]. Traditionally, assessment has been more associated to teaching and, therefore, to the teacher, following the accountability model.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Decisions made by schools influence their students' potential outcomes and chances, and the delayed effects of public examinations and evaluations are perhaps more critical [1]. More recently, it has been argued that evaluation methods in higher education require a change to include elements within the university didactic assessment strategies, such as co-assessment and self-assessment [2,3].…”
Section: Introductionmentioning
confidence: 99%